Electricity metering data exchange. The DLMS/COSEM suite. SMITP B-PSK PLC communication profile for neighbourhood networks. Including: The Original-SMITP PLC BPSK communication profile, The Original-SMITP Local data exchange profile and The Original-SMITP IP communication profile Part 8, (31st May 2015) - British Standards Institution,
No abstract available